KEPEMIMPINAN YANG MENAVIGASI KETIDAKPASTIAN DALAM PERDAGANGAN INTERNASIONAL DI ERA DISRUPSI PASAR GLOBAL - Anwar, Lathifah; Prasetya, Abim Arda; Avrilla, Vanessa Alicia Marsha; Anshori, Moh Isa (Journal of Information System, Applied, Management, Accounting and Research, 2025)
Rapid developments in technology, geopolitics, and regulatory changes have significantly intensified uncertainty in international trade, especially within the context of global market disruption. To address these challenges, leadership approaches grounded in established theoretical frameworks are essential. This article examines key leadership theories, including transformational leadership (Burns; Bass & Avolio), adaptive leadership (Heifetz et al.), and multicultural collaborative leadership (Rockstuhl et al.), to understand how leaders can navigate global complexity. Effective leaders are expected to inspire change, foster innovation, and promote cross-cultural collaboration to strengthen organizational resilience. Furthermore, Yukl’s theory emphasizes the role of innovation and synergy in responding to external disruptions. Findings from the literature indicate that integrating these theoretical approaches enables the formulation of dynamic and adaptive leadership strategies—such as identifying market trends, responding swiftly to regulatory shifts, and building resilient supply chains. This study not only reinforces the theoretical foundation of global leadership but also provides practical insights for international business leaders to manage uncertainty and adapt to rapidly changing global markets